The evolution of food and nutrition supply patterns of marine capture and mariculture in China and its transformation coping strategies - Qiao, Shouyi; Yin, Wei; Liu, Yuhao; Li, Dahai (Frontiers in Marine Science, 2024)
This study examines the shift in China’s seafood production, revealing that mariculture has surpassed marine capture as the primary source of marine food. The research aims to assess the roles of marine capture and mariculture in meeting rising food demand and ensuring nutrition security, given the limitations of land-based food production. Using data from 2003 to 2021, the study highlights several key trends: mariculture, focused on shellfish and algae, now outpaces marine capture, which remains centered on fish and crustaceans. Significant regional disparities are observed, with mariculture expanding rapidly in several coastal provinces as marine capture declines. Nutrient supply from marine capture has followed a three-phase pattern of growth, stagnation, and decline, while mariculture’s nutrient output has steadily increased, particularly in protein. By 2019-2020, mariculture surpassed marine capture in energy and protein supply, though fat supply remains lower. Regional differences in nutrient supply show mariculture leading in multiple provinces. The study concludes by recommending strategies to promote sustainable, diverse, and environmentally friendly practices for China’s marine food systems.